GRAFTING MALEAT ANHIDRAT PADA KARET ALAM SIKLIS (CYCLIC NATURAL RUBBER/CNR) DENGAN INISIATOR DICUMYL PEROKSIDA - Eddiyanto ,; M. Said Siregar; Ichlas Rawo Syaputra (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThe research on the degree of grafting of maleic anhydride (MA) on Cyclic Natural Rubber/CNR with the initiator Dicumyl Peroxide (DCP) has done. Grafting process carried out by reflux in a flask technique coupled with the base of the condenser and oil bath at a temperature of (105-110)°C, variations in the concentration of MA (3, 6, 9, 12, 15) phr, DCP variation inisiator concentration (0.05; 0.1; 0.15) molar ratio and variation in time (15, 30, 60, 90) minutes. Determination of the degree of grafting is then performed by the method of titration and FTIR spectra analysis to determine the grafting of MA on CNR chain. The results showed that the MA-g-CNR occurs at 15 phr comparison with the degree of grafting of 0.12% for the variation of the concentration of MA; 0.15 molar ratio to the degree of grafting of 0.07% for the variation in concentration of DCP inisiatior; 90 minutes with a degree grafting of 0.14% for the time variation.Keywords: grafting, cyclic natural rubber, maleic anhydride, dicumyl peroxide